Estratégias de tradução em um curso de licenciatura em letras : uma análise sob a perspectiva de Andrew Chesterman - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This dissertation, which is linked to the area of knowledge of Applied Linguistics, is the result of investigations about the use of translation strategies by undergraduate students of a course of Letras. We chose qualitative/interpretative research with emphasis on the naturalistic case study as a methodological basis to conduct this research. To carry out the study, we observed, catalogued and analyzed strategies used by students in interlingual translation processes of texts. It was adopted the taxonomy proposed by Chesterman (1997), which classifies the strategies into three distinct groups: Grammatical, Semantic and Pragmatic. Based on Jakobson (1971), Derrida (1972), Milton (1998), Arrojo (1996), Darim (1997), Paiva (2005), Prado (2008), Hatje-Faggion (2011), Alves, Magalhães and Pagano (2014), it was possible to establish dialogues between Translation Studies and teaching-learning of English as a foreign language in academic contexts. We also discuss the relevance of the contributions of collaborative activities in the process of collective translation of texts. For that, we rely on the socio-cultural theory (Vigostsky, 1978) and the studies carried out by Sabota (2002), Figueiredo (2012), among others. This research allowed us to understand the level of relations between the use of certain strategies and the mechanisms that students use to acquire the English language and, with this, to point out the metacognitive translation strategies as a way of monitoring actions and reflection on the decisions made in translation.
Keywords: Estratégias de tradução; Chesterman; Ensino-aprendizagem de línguas estrangeiras; Línguas inglesa e portuguesa; Translation strategies; Chesterman; Teaching an learning of foreign languages; English and portuguese languages; CIENCIAS HUMANAS::EDUCACAO; LETRAS::LINGUAS CLASSICAS